Producción de culantro coriandrum sativum l en suelos pesados en la granja experimental Santa Inés como materia prima para elaboración de fitofarmacos - Cuenca Encarnación, Danny Vinicio (2015)
This paper entitled "CULANTRO PRODUCTION (Coriandrum sativum L.) ON SOIL HEAVY IN EXPERIMENTAL FARM SANTA INES, AS RAW MATERIAL FOR DEVELOPMENT OF phytodrugs" raised objectives as (Determine the range of cilantro that produces the highest percentage of raw material for the preparation of herbal medicines and establish what stage of development the highest percentage of raw material is produced), the same farm was within Santa Inés, first locating the study area, and then make a cleaning this area presented a heavy soil clay texture, then proceeded to clean and suitability of soil for the adequacy proceeded to crush and loosening soil, then plot were constructed (the measures are 4m x 1.2m) where each plot is assigned a treatment. Crop management coriander no chemical fertilizers are used, by which it can be called an organic production. In this study three varieties of coriander (Slow Bolting Tyte, Anita and Long Standing) were evaluated and different harvest times the (35; 40; 45; 50; 55 days) after planting (DAP), the collection of sample was made boot, for which a complete randomized design (DCA) was used with a factorial arrangement 3x5, with four replications. This test served for slaughter for parallel research work with the Faculty of Chemistry and Health, also resulted internship class for students of the careers of Agricultural Engineering and Agricultural Economics. The best results are that the variety Long Standing in heavy clay soil texture, produced the highest percentage of raw material for the production of herbal medicines and harvesting stage at 55 DAP (days after sowing) produced greater amount of raw material. Also this variety produced more percentage amount of raw material in the two agronomic descriptors with respect to the stem (wet and dry) and leaves (wet and dry).